The role of psychological capital and social support in academic adjustment and psychological well-being in portuguese higher education (Revista Lusófona de Educação, 2025)
This study examines the impact of psychological capital and social support on the academic adjustment and psychological well-being of university students in Portugal. The research is based on the hypothesis that high levels of these variables are associated with better adaptation and psychological well-being in the university context. Following a quantitative approach with a sample of 210 students from various Portuguese universities, the results indicate a positive and significant correlation between psychological capital, social support, and psychological well being. Social support was identified as a mediator in the relationship between psychological capital and well-being, suggesting that students with higher psychological capital perceive greater social support, which contributes to their psychological well-being. The study concludes that both psychological capital, encompassing self-efficacy, optimism, resilience, and hope, and social support are crucial for students’ academic adjustment and well-being, recommending the implementation of institutional strategies to promote these dimensions.